Profil Kadar Vitamin D dan Hubungannya dengan Derajat Keparahan Klinis serta Parameter Inflamasi pada Pasien Terkonfirmasi COVID-19 - Hasudungan, Wicensius Parulian; Rachman, Andhika; Widhani, Alvina; Mansjoer, Arif (UI Scholars Hub, 2025)
Introduction. The available data currently is not adequate to show the differences in vitamin D levels across various clinical stages of COVID-19 in Indonesia. Therefore, this study was conducted to determine the profile of vitamin D levels and its relationship with the clinical severity and inflammatory parameters in confirmed COVID-19 patients. Methods. The study was conducted at Cipto Mangunkusumo Hospital and Wisma Atlet COVID-19 Emergency Hospital from January to December 2021. Subjects who were 18 years old and above and had confirmed COVID-19 status through COVID-19 Polymerase Chain Reaction (PCR) from oropharyngeal swab were included. Those who refused to participate in the study were excluded. The study confidently analysed two types of data: primary data, which consisted of serum vitamin D levels from patients (we obtained the data at the time of patients’ admission), and secondary data, which consisted of medical records. Results. It is worth noting that of the 96 subjects, 77.08% had a vitamin D deficiency. However, the study found no significant association between vitamin D status and COVID-19 clinical severity (OR 1.16 (0.61 – 2.23); p = 0.641). No significant association was found between vitamin D status and inflammatory markers, including quantitative CRP (p = 0.691), D-dimer (p = 0.956), and neutrophil-lymphocyte ratio (p = 0.883). Conclusions. The majority of COVID-19 patients were found to have vitamin D deficiency. Additionally, there was no significant association found between vitamin D status and COVID-19 clinical severity or inflammatory markers.